Compound-Specific Carbon Isotope Analysis of Polycyclic Aromatic Hydrocarbons in Water Using Solid-Phase Extraction Coupled with GC/C-IRMS - Zhang, Lin; Zhang, Yongtao; Liu, Fuliang; Liu, Jun (Asian Journal of Chemistry, 2014)
A method using solid-phase extraction coupled with gas chromatography/combustion/isotope ratio mass spectrometry (GC/C-IRMS) for the compound-specific stable carbon isotope analysis of polycyclic aromatic hydrocarbons in aqueous phase was developed in this study. Parameters for the efficient extraction of polycyclic aromatic hydrocarbons from water samples were evaluated by SPE-GC/MS. The results indicated that individual polycyclic aromatic hydrocarbons in water can be effectively separated from unresolved complex mixtures by the proposed procedure. The mean recovery of the purification method for all compounds is > 80 %. The carbon isotope composition of polycyclic aromatic hydrocarbons can be measured with a standard deviation of < 1 %, for standard material extracts after purification. No significant isotopic fractionation was observed during the solid-phase extraction procedure. These findings indicate that the solid-phase extraction-GC/C-IRMS method is well suited for the compound-specific carbon isotope analysis of polycyclic aromatic hydrocarbons in aqueous phase and can be used as a potential tool for the source identification of polycyclic aromatic hydrocarbons.